Bold & brave : ten heroes who won women the right to vote - Gillibrand, Kirsten, 1966- (Alfred A. Knopf, 2018)
Profiles ten women who fought hard to gain the right to vote in the United States, including Elizabeth Cady Stanton, Susan B. Anthony, Sojourner Truth, and Inez Milholland.